2016
DOI: 10.14238/pi45.2.2005.69-75
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of rotavirus diarrhea in the outpatient clinic of Cipto Mangunkusumo Hospital, Jakarta

Abstract: Background Rotavirus is one of the most common cause of acute

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…11 The incidence of diarrhea was higher in infant aged 6-11 months followed by children aged 12-24 months. 2 This is in accordance with the findings of Ariani et al 12 and Tjitrasari et al 13 in their studies at CM Hospital that the incidence rate of acute diarrhea was higher among the 6-11 months age group than that in the 12-24 months age group. Infants who are younger than 6 months are protected by transplacental antibody and breast feeding, whereas 80-100% of older children are protected by antibody produced by previous infection.…”
Section: Discussionsupporting
confidence: 87%
“…11 The incidence of diarrhea was higher in infant aged 6-11 months followed by children aged 12-24 months. 2 This is in accordance with the findings of Ariani et al 12 and Tjitrasari et al 13 in their studies at CM Hospital that the incidence rate of acute diarrhea was higher among the 6-11 months age group than that in the 12-24 months age group. Infants who are younger than 6 months are protected by transplacental antibody and breast feeding, whereas 80-100% of older children are protected by antibody produced by previous infection.…”
Section: Discussionsupporting
confidence: 87%
“…1 Another study also found that rotavirus diarrhea was 1.4 times more common in males than females. 6 In contrast, Kelkar et al found that there was no statistically significant difference in the incidence of rotavirus diarrhea in male and female children (62.9% vs. 60%, respectively). 7 To date, there is no explanation of how gender affects the prevalence of rotavirus diarrhea.…”
Section: Resultsmentioning
confidence: 92%
“…Tjitrasari et al reported the prevalences of cough and colds in patients with acute rotavirus diarrhea to be 51.9% and 46.0%, respectively. 6 Some studies have suggested that rotavirus infection may involve the Sen=sensitivity, spec=specificity, PPV=positive predictive value; NPV=negative predictive value; LLH+= positive likelihood ratio; LLH-= negative likelihood ratio; COP=cut-off point respiratory tract, hence, rotavirus may be spread through airborne droplets. Respiratory symptoms have been reported in 20-40% of patients with acute rotavirus diarrhea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The low incidence of rotavirus in children aged > 2 years can also explained by the presence of natural antibodies arising from recurrent infections of rotavirus. 13 Clinical manifestations of rotavirus infection include being asymptomatic, or having watery diarrhea and frequent vomiting, that can develop into mild to severe dehydration. In our study, the predominant symptom of vomiting was found to be significantly higher in the rotavirus-positive group than in the negative group (P<0.05).…”
Section: Resultsmentioning
confidence: 99%